Well-test deconvolution analysis of gas condensate layered reservoirs - Geravand, R. (Offshore Technology Conference, 2020)
Well testing, especially in offshore platforms, is quite expensive and traditional well-test analysis are not capable of fully capture the boundary dominated effects from short-time, constant-rate pressure buildups. The complexity of the well test behavior of gas condensate layered reservoirs causes the pressure data from drawdown flow periods become too noisy, which makes it extremely difficult to obtain accurate results using conventional well-test analysis. Hence, only build-up periods with unit flowrate are used in pressure transient analysis. However, the duration of build-up tests are hardly long enough to capture the boundary dominated effects / faults. Luckily, deconvolution approach has overcome this issue through converting the whole test periods including multiple drawdown and build-up periods into a constant-rate pressure drawdown. This work aims to apply the variable-rate deconvolution approach to analyze a series of short well-test data obtained from the single-layer drill stem tests (DSTs) carried out in an offshore gas condensate layered reservoir. The results demonstrated that compared to the pressure derivative method, the deconvolution analysis provided us with more range of data and increased the radius of investigation, which enabled us to identify the boundary dominated flow regimes such as leaky/partially communicating fault, sealing fault / no flow boundary, as well as constant pressure boundary at late-times. In addition, we evaluated the performance of the treatment job conducted during some DSTs, in the same reservoir. Copyright 2020, Offshore Technology Conference